Female Education in a Chan Public Monastery in China: The Jiangxi Dajinshan Buddhist Academy for Nuns - Campo, Daniela (Religions, 2022)
The Great Chan Monastery of the Golden Mountain (Dajinshan Chansi 大金山禪寺) is a large monastic complex for nuns located in Jiangxi province in southeast China and belonging to the Chan meditation school. The Jiangxi Dajinshan Buddhist Academy for Nuns (Jiangxi foxueyuan Dajinshan nizhong xueyuan 江西佛學院大金山尼眾學院), established at the monastery in 1994, is one of the few institutes for nuns in China to be especially axed on Chan studies and practice. What are the pedagogical goals and agenda of the Jiangxi Dajinshan Buddhist Academy for Nuns? What are the specificities of this academy as compared to other female academies, and to academies for monks? Why do nuns enroll at Dajinshan Buddhist Academy? What does this case study tell us about the gender balance in Chinese Buddhism today? This paper, based on fieldwork, will try to answer these questions by especially considering enrollment and scale, students and personnel, and curricula and schedule of the Jiangxi Dajinshan Buddhist Academy for Nuns.